Model of the Development of the Legal Culture of Children of the Risk Group in the Conditions of the Organization of Additional Education - Tulaboeva Gulorom Tulaboevna; Saydaliyeva Dilfuza Zairjanovna; Kurbanova Muxabbat Mamadjanovna; Mustayeva Guldora Salaxiddinovna (Zien Journals, 2022)
The problem of developing a legal culture, including for children at risk, is determined by the current state of crime among juveniles who were previously held accountable. In this regard, the need to identify factors in the development of this phenomenon and the possibility of eliminating these factors is to build a model for the development of legal culture. The article provides a brief overview of scientific research on the essence of legal culture in science. The paper gives a brief description of children at risk in order to build a qualitative model within the framework of a student-centered approach in education. The article presents a model for the development of legal culture for children at risk in the context of additional education with effective forms and methods of work
Keywords: legal culture; children at risk; development model; institution of additional education